2017
DOI: 10.1016/j.ajur.2016.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Prostate cancer screening in Europe and Asia

Abstract: Prostate cancer (PCa) is the second most common cancer among men worldwide and even ranks first in Europe. Although Asia is known as the region with the lowest PCa incidence, it has been rising rapidly over the last 20 years mostly due to the introduction of prostate-specific antigen (PSA) testing. Randomized PCa screening studies in Europe show a mortality reduction in favor of PSA-based screening but coincide with high proportions of unnecessary biopsies, overdiagnosis and subsequent overtreatment. Conclusiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 80 publications
1
51
0
1
Order By: Relevance
“…In the European Randomized Study of Screening for Prostate Cancer study, prostate cancer mortality was reduced by 21% in favor of the screening arm. In contrast, a recent publication by the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial data showed a 90% PSA contamination rate in the control arm, which seriously questions the value of the reported outcomes …”
mentioning
confidence: 88%
See 1 more Smart Citation
“…In the European Randomized Study of Screening for Prostate Cancer study, prostate cancer mortality was reduced by 21% in favor of the screening arm. In contrast, a recent publication by the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial data showed a 90% PSA contamination rate in the control arm, which seriously questions the value of the reported outcomes …”
mentioning
confidence: 88%
“…In contrast, a recent publication by the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial data showed a 90% PSA contamination rate in the control arm, which seriously questions the value of the reported outcomes. 2 Even among Asian countries, there were significant differences in the trends of prostate cancer death. In countries such as Australia, New Zealand, Japan and Singapore, where the exposure rate of PSA screening is relatively high, the number of prostate cancer deaths has decreased; however, in other countries such as the Philippines and Thailand, where PSA screening is rare, the death rate continues to increase.…”
Section: Editorial Commentmentioning
confidence: 99%
“…The early diagnosis of pre-invasive and metastatic tumour cells in patients is pivotal for the judicious choice of treatment and success of therapies and for the improvement of survival rates. Early diagnosis of Pca is usually reliant on techniques that include digital rectal examination, magnetic resonance imaging and transrectal ultrasound-guided biopsy in conjunction with screening for serum levels of prostate specific antigen (PSA) which remains the principal biomarker for Pca (Zhang et al 2017). A challenge across the spectrum of cancers is to identify and incorporate into clinical practice, well-defined and validated diagnostic and predictive biomarkers of disease (Dijkstra et al 2012;Hemminki et al 2012;Selvolini and Marrazza 2017;Ueland 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Allerdings scheint der Anstieg der PCa-Inzidenz nach Beginn der EinfĂŒhrung des PSA-Screenings in Asien stĂ€rker ausgeprĂ€gt zu sein als in Europa (Ferlay et al 2015;Zhang et al 2017 (Potosky et al 1990). Danach fĂŒhrte der Start von Screening-Programmen mit prostataspezifischem Antigen (PSA) zu einem zweiten deutlichen Schaden-VerhĂ€ltnis und die Kostenwirksamkeit dieser neuen Verfahren zu ermitteln.…”
Section: Introductionunclassified